FLLL12 induces apoptosis in lung cancer cells through a p53/p73-independent but death receptor 5-dependent pathway. Issue 2 (28th July 2015) - Haque, Abedul; Rahman, Mohammad A.; Fuchs, James R.; Chen, Zhuo Georgia; Khuri, Fadlo R.; Shin, Dong M.; Amin, A.R.M. Ruhul
Highlights: In this manuscript, we have shown for the first time that the synthetic curcumin analog FLLL12 is 5–10-fold more potent than natural curcumin against a panel of eight lung cancer cell lines, and induces apoptosis. Moreover, using siRNA-mediated gene silencing, for the first time, we reveal that ablation of DR5, caspase 8 and Bid significantly protected lung cancer cell lines from FLLL12-induced apoptosis. Interestingly, the expression of DR5 is specific for FLLL12, as curcumin does not induce the expression of DR5. We further demonstrate that FLLL12 regulates DR5 at a posttranscriptional level through activation of protein tyrosine phosphatases, as blocking of protein tyrosine phosphatases with chemical inhibitors blocked the expression of DR5 and significantly protected cells from FLLL12-induced apoptosis. We believe that we demonstrate a set of novel observations in this manuscript as mentioned above. Abstract: Unlike chemotherapy drugs, the safety of natural compounds such as curcumin has been well established. However, the potential use of curcumin in cancer has been compromised by its low bioavailability, limited tissue distribution and rapid biotransformation leading to low in vivo efficacy. To circumvent these problems, more potent and bioavailable analogs have been synthesized. In the current study, we investigated the mechanism of anti-tumor effect of one such analog, FLLL12, in lung cancers. IC50 values measured by sulforhodamine B (SRB) assay at 72 h and apoptosis assays (annexin V staining, cleavage of PARP and caspase-3) suggest that FLLL12 is 5–10-fold more potent than curcumin against a panel of premalignant and malignant lung cancer cell lines, depending on the cell line. Moreover, FLLL12 induced the expression of death receptor-5 (DR5). Ablation of the expression of the components of the extrinsic apoptotic pathway (DR5, caspase-8 and Bid) by siRNA significantly protected cells from FLLL12-induced apoptosis (p < 0.05). Analysis of mRNA expression revealed that FLLL-12 had no significant effect on the expression of DR5 mRNA expression. Interestingly, inhibition of global phosphatase activity as well as protein tyrosine phosphatases (PTPs), but not of alkaline phosphatases, strongly inhibited DR5 expression and significantly inhibited apoptosis (p < 0.05), suggesting the involvement of PTPs in the regulation of DR5 expression and apoptosis. We further showed that the apoptosis is independent of p53 and p73. Taken together, our results strongly suggest that FLLL12 induces apoptosis of lung cancer cell lines by posttranscriptional regulation of DR5 through activation of protein tyrosine phosphatase(s).